PENGARUH PAJAK PENGHASILAN DAN ASSET PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PROPERTY & REALESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) (Students' Journal of Accounting and Banking, 2015)
The purpose of this study to determine how the effect of income tax as well as the size of the firm on earnings management. Purposive sampling method was selected from as many as 94 companies sector Property & Realestate as the study sample. The sampling technique used is the documentation. Methods of data analysis using multiple linear regression analysis. The results of multiple linear regression showed a significant negative effect of income tax on earnings management, where the tax is not the main reason for the company to act earnings management. Firm size shows a significant positive effect on earnings management, which reflects the company's increasingly motivate earnings management measures.Keywords: Earnings Management, Income Tax, Company Size